If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6y = 92 Solving 5x + 6y = 92 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 5x + 6y + -6y = 92 + -6y Combine like terms: 6y + -6y = 0 5x + 0 = 92 + -6y 5x = 92 + -6y Divide each side by '5'. x = 18.4 + -1.2y Simplifying x = 18.4 + -1.2y
| 10-3n=1 | | 5x+3+6x=9+4x+8 | | 12-2n=8n+4 | | 5-w/6=22 | | -[4z-(15z+4)]=4+(10z+2) | | (y+0)=0.5(x-3) | | 8x^2=162 | | 4-5*n=21 | | (5b-4)-2(2b+1)=-2 | | 3(x+1)+2x=24 | | 4(x-0.66)=-18 | | 4k-7=k-10 | | -24+10=m-5 | | 7x-35=-2(-8x+4) | | 15=5-n | | 17=-5 | | 8x+1=-16 | | -6x+4(x-4)=-14 | | 72c=8 | | 26-(x-11)=-5(x+7) | | 5m+2m-5= | | x/-13=-40 | | w=2x^2-yz | | y=0.5x+1.5 | | 14*30+d=-196 | | (4+1)+2= | | 8y+2=21 | | 14+30+d=-196 | | 3=x(9-2x)(6-2x) | | 20=s-5 | | 7x+9+3x+1=8x-5 | | 8x-11=-5 |